Investigating the Role of Gut Microbiota in Pediatric Patients with Severe COVID-19 or MIS-C - Elena Franchitti; Paolo Bottino; Francesca Sidoti; Andrea Carpino; Giulia Pruccoli; Ugo Ramenghi; Cristina Costa; Ugo Ala; Emilia Parodi; Deborah Traversi (Microorganisms)
Severe COVID-19 and MIS-C are rare but serious outcomes associated with SARS-CoV-2 infection. The onset of MIS-C often involves the gastrointestinal system, suggesting a potential connection with gut microbiota. This study aims to compare the gut microbiota of children with severe COVID-19 and those with MIS-C using various biomolecular approaches. Gut microbiota composition and specific microbial modulations were analyzed using fecal samples collected at hospital admission. The study included hospitalized patients (mean age 6 ± 5 years) diagnosed with severe COVID-19 (37 patients) or MIS-C (37 patients). Microbial differences were assessed using both NGS and qRT-PCR methodologies. In 75% of cases, pharmacological treatments included antibiotics and corticosteroids, which influenced the microbiota composition. Early age was found to have the most significant impact on microbiota diversity. Significant differences in alpha and beta diversity were observed between COVID-19 and MIS-C patients, particularly concerning low-abundance species. Levels of Bacteroides spp., Bifidobacterium spp., and Akkermansia muciniphila were comparable between groups, while an increased activity of Bifidobacterium spp. was noted in children with positive fecal samples (p = 0.019). An in-depth evaluation of lesser-known gut species may be key to reducing the risk of severe outcomes and developing microbiota-based biomarkers for the early diagnosis of MIS-C.